Field notes contributed by Dennis L. Carter, August 2, 1997 - Carter, Dennis L.et al (1997)
Summer report of birds contributed by Dennis L. Carter. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1997. Epson - sheet feed/flatbed